KEBIJAKAN PENGELOLAAN BARANG MILIK DAERAH DI KABUPATEN LAMPUNG UTARA - Sriyani; Arifah Fibri Andriani; Ria Dewi Ambarwati (Halu Oleo University, 2025)
The purpose of this study is to evaluate the implementation of regional asset management in the North Lampung Regency, identify the strengths and weaknesses of regional asset management in the North Lampung Regency Government, and develop strategies for optimising regional asset management in North Lampung. This research is a qualitative study with a descriptive approach. Based on the results of the analysis conducted on the management of Regional Assets (BMD) in North Lampung Regency, overall BMD management is in the